Philosophy of religion - "Kanal, S.P." (New Delhi, 1984)
The book is really an introduction to contemporary religious philosophy and is a helpful guide to the students. The modern relevance of Advaitism has been given its rightful claim in the book. It is a ripened fruit of the preoccupation of the author with religious philosophy for more than fifty years preface to the second edition, definition of religion, religion and other eisciplines, metaphysical theories of religion, foundation of religious belief, religious knowledge and language, A General View of Religion and Language, Proofs for the Existence of God, The Ontological Argument, Cosmological Argument, Teleological Argument, The Argument from Religious Experience, The moral Argument for the Existence of God, The philosophy of theism, The Attributes of God, The problem of evil, The problem of Immortality, The encounter of Religions, index.
Keywords: Religion